Start learning today, and be successful in your academic & professional career. Start Today!

• ## Related Books

 0 answersPost by Veasna Mam on June 10 at 12:25:42 AMFor some reason the video does not load it says network error. smh 1 answerLast reply by: Professor Fung Mon May 18, 2015 12:06 AMPost by Lee Ross on May 14 at 01:18:02 PMHi Nancy. Just a question regarding your "Extra Example 2". You multiply 4.3(5.2+x) first. Can you explain why you don't do the brackets first? The 5.2+x. Thanks, And great lessons BTW :) 1 answerLast reply by: Professor Fung Wed Jan 16, 2013 1:30 AMPost by bo young lee on January 15, 2013i dont understand the how to simplify the expression. 0 answersPost by Derrick Lu on June 30, 2012

### Simplifying Algebraic Expressions

• A term is a number, a variable, or the product of a number and one or more variables. The terms of an algebraic expression are separated by plus and minus signs.
• You can combine terms when they are like terms. Like terms are those that have exactly the same variable factors.
• There is a coefficient of 1 in front of a variable that does not have any numeric coefficient. For example you can write 1x as x or −1y as −y.

### Simplifying Algebraic Expressions

3x + x − 12x =
• 4x − 12x =
− 8x
− 6x − 3x =
− 9x
Larissa buys 3 drinks for a party. Michael buys 5 drinks for the party. Nick buys 7 drinks for the party. Write and simplify an algebraic expression to represent the total cost of the drinks.
• Let d = cost of one drink.
• 3d + 5d + 7d =
15d
In one trip to the store, you buy 2 oranges. On the second trip, you buy 7 more oranges. Write and simplify an algebraic expression to represent the total cost of oranges.
• Let c = cost of an orange.
• 2c + 7c =
9c
3x + 4(x − 6) =
• 3x + 4x − 24 =
7x − 24
8(2y − 3) + 8y =
• 16y − 24 + 8y =
24y − 24
6x − 10 + 2x + 13 =
8x + 3
1.2(4 + x) − 3.4x =
• 4.8 + 1.2x − 3.4x =
4.8 − 2.2x
Eric fed his dog 5 dog treats, his sister fed the dog 2 dog treats, and his brother fed the dog 9 dog treats. Write and simplify an algebraic expression to represent the total amount of calories the dog consumed.
• Let c = calories in one dog treat.
• 5c + 2c + 9c =
16c
[1/4](16x + 12) − 5 + 2x =
• 4x + 3 − 5 + 2x =
6x − 2

*These practice questions are only helpful when you work on them offline on a piece of paper and then use the solution steps function to check your answer.